2012
DOI: 10.4103/0970-2113.99104
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance profiles of Mycobacterium tuberculosis isolates to first line anti-tuberculous drugs: A five years study

Abstract: Background:Drug resistance is a major problem in the treatment of tuberculosis (TB). An estimate of drug resistance is extremely important in the epidemiology and control of TB. However, an assessment of the magnitude of drug resistance in TB is not very well described globally and data remains scantier for India. In view of this, we reviewed our data over last five years.Materials and Methods:Six hundred and seventy-three Mycobacterium tuberculosis isolates were subjected to drug susceptibility against primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 3 publications
2
20
1
1
Order By: Relevance
“…[6][7][8][9][10][11][12] To obtain a more precise estimate of Multi-Drug Resistant TB (MDR-TB) burden in the country, RNTCP carried out drug resistance surveillance (DRS) surveys in accordance with global guidelines in selected states, Gujarat (56 million population) and Maharashtra (107 million) in 2005-2006 and Andhra Pradesh (81 million) in 2007-2008. The results of these surveys indicate prevalence of MDR-TB to be low i.e., less than 3% amongst new cases and 12-17% in re-treatment cases.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] To obtain a more precise estimate of Multi-Drug Resistant TB (MDR-TB) burden in the country, RNTCP carried out drug resistance surveillance (DRS) surveys in accordance with global guidelines in selected states, Gujarat (56 million population) and Maharashtra (107 million) in 2005-2006 and Andhra Pradesh (81 million) in 2007-2008. The results of these surveys indicate prevalence of MDR-TB to be low i.e., less than 3% amongst new cases and 12-17% in re-treatment cases.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction Tuberculosis(TB), a disease caused by Mycobacterium tuberculosis, has affected mankind for over 5000 years, and still continues to be a leading cause of morbidity and mortality. 1 The emergence of resistance to anti-tubercular drugs in general is a significant public health problem that threatens tuberculosis care and control worldwide. Multi-drug-resistant tuberculosis (MDR-TB) is defined as tuberculosis that is resistant to at least Isoniazid (INH) and Rifampicin (RMP), the two most powerful first-line treatment anti-TB drugs.…”
mentioning
confidence: 99%
“…The advent of HIV/AIDS contributed to these substantially. 1 Epidemiological studies for MDR-TB is important to optimize drug therapy and prevent the dissemination of resistant strains in the community. With this background the present study was undertaken with the following objectives:…”
mentioning
confidence: 99%
“…The drug resistance pattern showed a higher rate of panresistant isolates (50.6%) which is very high compared with previous large-scale studies and an indicative factor of XDR-TB emergence. [28][29][30] Mutation analysis of RIF resistance showed a domination of rpoB codon 531 (77.1%) followed by codon 526 (13.2%). This finding distinctly reflects the conclusions of one of our recent nationwide study and other reports which showed high rate of mutation in codon 531 as the main cause of RIF resistance in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%